Archaeometrical research of lithic raw materials for early neolithic prehistoric communities with the help of prompt gamma activation analysis : the aims of project, current achievements and future perspectives - Težak-Gregl, Tihomila (Array, 2009)
After two initial years of work on Hungarian-Croatian project "Archaeometrical research of lithic raw materials for early Neolithic prehistoric communities with the help of Prompt Gamma Activation Analysis, with special regard to radiolarites and obsidians", this paper brings part of its outcomes: current achievements and guidelines for future steps from Croatian perspective. The very first petrographical analyses of Neolithic obsidian and radiolarites excavated on Croatian soil were covered with this research. Also, a few accessible samples from Bosnia and Herzegovina were also processed for a first time. Authors suggest a potential obsidian data-base in which all (or part of) known information of analyzed samples would be stored and accessible via Internet.